Pengembangan Sistem Cetak Resi Pada Toko Nazra SHA Menggunakan Extreme Programming Untuk Efektifitas Pembuatan Resi - Naeska Fahira, Syelvi; Ariesandes, Thoty; Febi Atmaja, Yoga; Lutfi Fuadi, Achmad (CV. Shofanah Media Berkah, 2025)
This research focuses on the design and development of CetakResi, an Android-based application for recording and printing shipping receipts. The system aims to assist business owners in managing the shipping process efficiently and systematically. The application was developed using the Extreme Programming (XP) methodology, which emphasizes rapid iterations, continuous user involvement, and frequent improvements. The development process includes planning, design, coding, testing, and user feedback. Key features of the application include shipment data entry, customer list management, automatic receipt generation, and transaction history tracking. With the implementation of CetakResi, the previously manual process of recording shipments can be minimized in terms of errors and significantly improved in terms of efficiency. This application is expected to be a practical and adaptive solution, especially for online sellers and small business owners.